Understanding employee branding capability and country-of-origin image impacts for internationalised firms - Bassi Suter, Mariana; Borini, Felipe; dos Santos-Costa, Lucas; Glaister, Alison; Meneses, Raquel; Johnston, Nathalie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2024)
This article focuses on understanding the role of employee branding capability (EmpBCap) in leveraging country-of-origin image (COI) as a firm resource. Drawing from the resource-based theory and signalling theory, we identify that EmpBCap enhances COI as a country-specific advantage (COI-CSA). Three sets of data were gathered, with 1,060 observations of executives working within internationalised Portuguese and Brazilian firms. Using psychometric procedures and SEM, the findings show that EmpBCap capability is an antecedent of COI-CSA and exerts an indirect effect on firm performance. The article extends previous research on COI from the supplier perspective by addressing calls for COI management research and provides further knowledge on internal brand management.